2011
DOI: 10.1017/s0007114511002121
|View full text |Cite
|
Sign up to set email alerts
|

Oil palm vegetation liquor: a new source of phenolic bioactives

Abstract: Waste from agricultural products represents a disposal liability, which needs to be addressed. Palm oil is the most widely traded edible oil globally, and its production generates 85 million tons of aqueous by-products annually. This aqueous stream is rich in phenolic antioxidants, which were investigated for their composition and potential in vitro biological activity. We have identified three isomers of caffeoylshikimic acid as major components of oil palm phenolics (OPP). The 2,2-diphenyl-1-picrylhydrazyl a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
80
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(82 citation statements)
references
References 41 publications
2
80
0
Order By: Relevance
“…OPP contains numerous phenolic acids including three isomers of caffeoylshikimic acid, protocatechuic acid and p -hydroxybenzoic acid. The detailed composition of OPP is as described earlier [22]. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…OPP contains numerous phenolic acids including three isomers of caffeoylshikimic acid, protocatechuic acid and p -hydroxybenzoic acid. The detailed composition of OPP is as described earlier [22]. …”
Section: Methodsmentioning
confidence: 99%
“…Water-soluble phenolics extracted from the oil palm vegetation liquor [21], termed oil palm phenolics (OPP) [22], also showed significant biological activities against cancer cells in vitro [23] and in vivo [23,24]. In relation to this, we previously reported a microarray analysis carried out on tumours which developed in BALB/c mice following subcutaneous injection of syngeneic J558 myeloma cells, which revealed that oral supplementation of OPP at 1,500 ppm gallic acid equivalent in these tumour-bearing animals caused a G1/S phase cell cycle arrest in the tumours [24].…”
Section: Introductionmentioning
confidence: 99%
“…Red PO is one of the richest sources of vitamin E (tocotrienols 70%-80% and tocopherols 20%-30%) (Mukherjee and Mitra, 2009) and carotenoids of which 80%-90% is present as α-carotene and β-carotene (Benadé, 2013). It also contains appreciable amounts of phospholipids, ubiquinones, sterols, and squalene (Choo et al, 2005) and phenolic compounds (Sambanthamurthi et al, 2011). The micronutrient in PO especially in the red PO has been found to have potent protective effects against chronic diseases, that is, cardiovascular disease, diabetes, and cancer (Che Idris et al, 2014;Benadé, 2013).…”
Section: Microencapsulated Palm-based Productsmentioning
confidence: 99%
“…This hypothesis is supported by our observation that addition of palm fruit juice (PFJ) to AZT-treated cultures reduced the number of drug-induced mtDNA mutations. Palm fruit juice is a water soluble by-product of oil extraction from the fruit of the oil palm (Elaeis guineensis) that is rich in antioxidant phenolics and other phytochemicals [15]. In particular, PFJ exhibits a high scavenging activity for hydrogen peroxide, the main reactive oxygen species produced in excess by defective mitochondria [16].…”
Section: Introductionmentioning
confidence: 99%